LLM-Powered News Research Tool for Equity Analysis - Thrivikram Bhat V,; Shubham Pathak,; Tanvi Bareja,; Mamta Sen,; Mrs Sindhu N, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As financial markets evolve, extracting timely and actionable insights from news content becomes increasingly critical for equity analysis and investment strategies. The surge in unstructured financial data poses a significant challenge for traditional analysis techniques. This survey investigates how Large Language Models (LLMs) can be harnessed to automate and enhance the interpretation of financial news. We explore a broad range of recent advancements, evaluate system frame- works, identify key obstacles, and discuss promising solutions. Our goal is to illuminate how LLMs are reshaping the landscape of financial analytics and to inspire continued innovation in this space.
Keywords: Large Language Models; News Analytics; Equity Research; Sentiment Analysis; Financial Technology; Natural Language Processing